2014
DOI: 10.1523/jneurosci.2489-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Dopamine Release in the Rat Nucleus Accumbens Symmetrically Encodes a Reward Prediction Error Term

Abstract: Making predictions about the rewards associated with environmental stimuli and updating those predictions through feedback is an essential aspect of adaptive behavior. Theorists have argued that dopamine encodes a reward prediction error (RPE) signal that is used in such a reinforcement learning process. Recent work with fMRI has demonstrated that the BOLD signal in dopaminergic target areas meets both necessary and sufficient conditions of an axiomatic model of the RPE hypothesis. However, there has been no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
240
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 254 publications
(265 citation statements)
references
References 29 publications
16
240
2
Order By: Relevance
“…Consistent with previous reports (Hart et al, 2014;Tobler et al, 2005), phasic dopamine activity was modulated by reward size and expectation in both groups in a manner consistent with the reporting of a reward prediction error from formal models of reinforcement learning, with increased phasic dopamine signaling after better-than-expected outcomes and decreased phasic dopamine signaling after worse-thanexpected outcomes. Interestingly, our data showed that adolescent alcohol consumption promoted a greater sensitivity to the unexpected variation in reward sizes.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous reports (Hart et al, 2014;Tobler et al, 2005), phasic dopamine activity was modulated by reward size and expectation in both groups in a manner consistent with the reporting of a reward prediction error from formal models of reinforcement learning, with increased phasic dopamine signaling after better-than-expected outcomes and decreased phasic dopamine signaling after worse-thanexpected outcomes. Interestingly, our data showed that adolescent alcohol consumption promoted a greater sensitivity to the unexpected variation in reward sizes.…”
Section: Discussionsupporting
confidence: 89%
“…This null result holds even at lower sample sizes (n ≅ 200 per category, randomly sampled). Prior work strongly supports the hypothesis that dopamine fluctuations in striatum should track RPEs (1,8,10,11,13,14). Our results contradict this expectation; however, the task we use was designed to also assess the impact of counterfactual feedback (e.g., difference between actual outcomes and what might have happened; Eq.…”
Section: Significancesupporting
confidence: 68%
“…Experiments in animal models support the hypothesis that changes in dopamine release at target neural structures encode reward prediction errors (RPEs) (the difference between actual and expected outcomes) important for learning and value-based decision-making (1,(8)(9)(10)(11)(12). In support of this claim, direct recordings of spike activity in mesencephalic dopaminergic neurons in nonhuman primates demonstrate that these neurons encode prediction errors in future reward delivery (8-10, 13, 14) and they may also encode other computations relevant for reward-guided actions (1,(15)(16)(17).…”
mentioning
confidence: 96%
“…Although the predominant evidence for RPEs comes from DA neuron electrophysiology, a few voltammetry studies, including that described above (albeit modulated by action), have largely provided converging support for these bidirectional signals 10 . However, voltammetry measurements exhibit slow drifts across time, and the documented phasic signals are hence always evaluated relative to the pre-cue baseline.…”
mentioning
confidence: 98%
“…One possibility is that tonically active neurons, a cholinergic population that pause during windows of dopaminergic RPEs, may signal when to learn and can further enhance the contrast between tonic and phasic DA signals 13 , although this remains speculative. Finally, on a broader level, RPE theory has been so successful in part because it has generated clear and testable predictions, leading to experimental designs that parametrically manipulate factors that affect RPE with compelling results 14 , even satisfying an axiomatic description of RPEs independent of any specific implementation 10 . Moreover, RPE models can still show ramping under certain circumstances and depending on assumptions 15 , so some purists may prefer the parsimony of a single RPE mechanism until further evidence for value theory accrues.…”
mentioning
confidence: 99%